(untitled) (Research, Society and Development, 2020)
Each year the amount of pesticides released into the environment grows, mainly contaminating the aquatic environment. Since glyphosate is the most widely used herbicide, many articles seek to understand the risks that this compound can provide in these areas. Therefore, the objective of this work was to characterize the methods applied in experimental studies in vivo in fish contaminated by glyphosate and their commercial formulations. The program StArt was used for screening articles were selected for an exploratory analysis and for screening, the StArt software was used, with a total of 3730 articles selected, from the ScienceDirect platform (n = 1018), ScieLO (339) and Scopus (2373). Of these, 121 articles were approved to search for the information that best answers the objective of this work. The first published work on in vivo contamination in fish was in 1979. Since then, around 8163 fish specimens have been used, the most used being Cyprinus carpio (n = 1758) and among the highest standard deviation values in relation to fish density per liter of water, weight and length (n = 10.54; 8.42; and 79.44 respectively). The most used concentration ranged from 0.0007 to 975 mg / L and the most used herbicide was Roundup Original®. It was noted the need for more detailed studies in relation to the methods applied and directed to more aggressive active principles, which are applied on a large scale in the environment and that studies aimed at systematizing publications are important for decision making by the public authorities in toxicological evaluations for registration or reassessments of pesticides.